Assessment of Trends in Non-Restorative and Preventative Dental Treatment Pre- and Post-COVID-19: A Health Informatics Pilot Study - Tanner Gamble; Carter Wilkerson; Cindy Kim; Karl Kingsley; Victoria Sullivan (Children)
Background/Objectives: The implementation of preventive treatments in pediatric dental care has been a priority in recent years. Understanding the factors that influence the timing and frequency of childhood preventive treatments, such as the impacts of the COVID-19 pandemic, are the focus of many health informatics researchers. Methods: A retrospective study was approved to assess changes in specific preventive treatments at a pediatric dental school clinic (sealants, fluoride varnish, and silver diamine fluoride) in the three years prior to (2017–2019) and following the COVID-19 pandemic (2020–2022). Results: A detailed analysis of these data revealed significant and unexpected shifts in these preventive services, with significant increases in dental sealants from pre- to post-pandemic (35.1%, p = 0.012), but corresponding decreases in other preventive treatments, such as the number of fluoride varnish (−37.6%, p = 0.011) and SDF treatments (−24.0%, p = 0.032), among this patient population. Conclusions: These data suggest that the selective pursuit of particular preventive dental services and treatments rather than others and understanding these shifts might help health informatics and dental public health researchers understand which factors influenced these decisions and behaviors, such as long-term durability and efficacy (sealants) or changing public perceptions of safety (fluoride and SDF).